Sodium selenite inhibits cervical cancer growth via ROS mediated AMPK/FOXO3a /GADD45a axis. (1st November 2022) - Qi, Lei; Wang, Yuanyuan; Su, Shengqi; Wang, Mingxing; Jablonska, Ewa; Jia, Yuehui; Wang, Ruixiang; Hao, Shuxiu; Feng, Chen; Li, Guijin; Jiang, Meijing; Du, Linlin; et al.
Abstract: Selenium is a trace element that has been shown to inhibit the growth of various cancer cell types. However, its role in cervical cancer and its underlying mechanisms remains largely unknown. Herein, we explored the anti-cervical cancer effect of selenium and its potential mechanisms through xenograft and in vitro experiments. HeLa cell xenografts in female nude mice showed tumor growth retardation, with no obvious liver and kidney toxicity, after being intraperitoneally injected with 3 mg/kg sodium selenite (SS) for 14 days. Compared to the control group, selenium levels in the tumor tissue increased significantly after SS treatment. In vitro experiments, SS inhibited the viability of HeLa and SiHa cells, blocked the cell cycle at the S phase, and enhanced apoptosis. RNA-sequencing, Kyoto encyclopedia of genes and genomes pathway analysis showed that forkhead box protein O (FOXO) was a key regulatory signaling pathway for SS to exhibit anticancer effects. Gene Ontology analysis filtered multiple terms associated with apoptosis, anti-proliferation, and cell cycle arrest. Further research revealed that SS increased intracellular reactive oxygen species (ROS) and impaired mitochondrial function, which activated adenosine 5'-monophosphate (AMP)-activated protein kinase (AMPK) via phosphorylation at Thr172, resulting in activation of FOXO3a and its downstream growth arrest and DNA damage-inducible alpha (GADD45a). In summary, SS exhibited anti-cervical cancer effects, and their mechanisms may be that SS is involved in inducing cell cycle arrest and potentiating cell apoptosis caused by ROS-dependent activation of the AMPK/FOXO3a/GADD45a axis. Highlights: SS inhibited HeLa cell xenograft growth with no obvious liver and kidney toxicity. SS induced HeLa and SiHa cell cycle arrests in the S phase and apoptosis. FOXO is a key regulatory signaling pathway for SS to exhibit anticancer effects. SS increased the ROS generation and damaged mitochondrial function. SS triggered the ROS-mediated AMPK/FOXO3a/GADD45a axis to exert anticancer effects.